Examining differential item functioning trends for English language learners in a reading test: A meta-analytical approach. (January 2014) - Koo, Jin; Becker, Betsy Jane; Kim, Young-Suk
In this study, differential item functioning (DIF) trends were examined for English language learners (ELLs) versus non-ELL students in third and tenth grades on a large-scale reading assessment. To facilitate the analyses, a meta-analytic DIF technique was employed. The results revealed that items requiring knowledge of words and phrases in context favored non-ELLs in grade 3, whereas items requiring evaluation skills favored ELLs in grade 10. However, inconsistent patterns were found across gender and ethnicity. Educational implications are discussed.